Describing language - Graddol, David (Open University Press, 1994)
A student introduction to descriptive linguistics, Describing Language is essentially practical in its orientation. It is useful for anyone who wishes to refer to technical literature involving linguistic description, who requires a basic conceptual framework and technical vocabulary with which to discuss language, and who needs to make elementary but principled descriptions and analyses of real data (such as classroom interaction or counselling sessions).